The Incidence of Infection Complicating Snakebites in Tropical Australia: Implications for Clinical Management and Antimicrobial Prophylaxis - Laura K. Smith; John Vardanega; Simon Smith; Julian White; Mark Little; Josh Hanson (Journal of Tropical Medicine)
Objective. To define the incidence of infection following snakebite in tropical Australia and the resulting implications for the routine prescription of prophylactic antibiotics. Methods. A retrospective study of all individuals presenting to Cairns Hospital, a tertiary referral hospital in tropical Australia, after a snakebite between December 2013 and October 2020. Results. There were 732 hospitalisations, 720 (98.4%) patients presented within 8 hours of the snakebite, and 29/732 (4.0%) were envenomated. Envenomated patients were more likely to receive empirical antibiotics than nonenvenomated patients (8/29 (27.6%) versus 14/703 (2.0%), p<0.001), although this was frequently as a bundle of care for critically ill individuals. Superficial skin infection was diagnosed by clinicians in 6/732 (0.8%) patients during their hospitalisation; infection was diagnosed more commonly in envenomated than in nonenvenomated patients (3/29 (10.3%) versus 3/703 (0.4%), p=0.001). All 3 envenomated individuals diagnosed with infection were believed to have taipan (genus Oxyuranus) bites. Five (83%) of the six patients diagnosed with infection had received empirical antibiotics at presentation; only 1/710 (0.1%) patients who received no antibiotics developed a (superficial) infection. Conclusion. Infection is a very uncommon complication of snakebite in tropical Australia. Individuals bitten by snakes in tropical Australia should not routinely receive antibiotic prophylaxis.